Tpeak‐Tend, Tpeak‐Tend/QT ratio and Tpeak‐Tend dispersion for risk stratification in Brugada Syndrome: A systematic review and meta‐analysis. Issue 6 (10th September 2018) - Tse, Gary; Gong, Mengqi; Li, Christien Ka Hou; Leung, Keith Sai Kit; Georgopoulos, Stamatis; Bazoukis, George; Letsas, Konstantinos P.; Sawant, Abhishek C.; Mugnai, Giacomo; Wong, Martin C.S.; Yan, Gan Xin; Brugada, Pedro; et al.
Abstract: Background: Brugada syndrome is an ion channelopathy that predisposes affected subjects to ventricular tachycardia/fibrillation (VT/VF), potentially leading to sudden cardiac death (SCD). Tpeak ‐Tend intervals, (Tpeak ‐Tend )/QT ratio and Tpeak ‐Tend dispersion have been proposed for risk stratification, but their predictive values in Brugada syndrome have been challenged recently. Methods: A systematic review and meta‐analysis was conducted to examine their values in predicting arrhythmic and mortality outcomes in Brugada Syndrome. PubMed and Embase databases were searched until 1 May 2018, identifying 29 and 57 studies. Results: Nine studies involving 1740 subjects (mean age 45 years old, 80% male, mean follow‐up duration was 68 ± 27 months) were included. The mean Tpeak ‐Tend interval was 98.9 ms (95% CI: 90.5‐107.2 ms) for patients with adverse events (ventricular arrhythmias or SCD) compared to 87.7 ms (95% CI: 80.5‐94.9 ms) for those without such events, with a mean difference of 11.9 ms (95% CI: 3.6‐20.2 ms, P  = 0.005; I 2  = 86%). Higher (Tpeak ‐Tend )/QT ratios (mean difference = 0.019, 95% CI: 0.003‐0.036, P  = 0.024; I 2  = 74%) and Tpeak ‐Tend dispersion (mean difference = 7.8 ms, 95% CI: 2.1‐13.4 ms, P  = 0.007; I 2  = 80%) were observed for the event‐positive group. Conclusion: Tpeak ‐Tend interval, (Tpeak ‐Tend )/QT ratio and Tpeak ‐Tend dispersion were higher in high‐risk than low‐risk Brugada subjects, and thus offer incremental value for risk stratification.